Arrest de la cour de parlement : contre le prince de Condé, & autres princes, seigneurs, & gentils-hommes, qui sans permission du roy, & contre son auctorité, depuis son absence ont pris les armes, & commettent tous actes d'hostilité, qui vont à la ruine & desolation de son pauure peuple. - France. Parlement (Paris); Morel, Fédéric, approximately 1552-1630; Mettayer, Pierre, -1639; Du Tillet (A Paris : Par Fed. Morel, & P. Mettayer, imprimeurs ordinaires du roy, 1615)
"This pamphlet constitutes the official condemnation of Condé and his followers for having left the court and rebelled against the authority of the Crown. "Faict en Parlement le dix-huictiesme Septembre, mil six cens quinze." It censures the rebelling princes and forbids all who may join them from taking up arms and assisting them"--French Political Pamphlets Digital Collection, Brigham Young University.
Variant of Lindsay, R.O. French political pamphlets, 1547-1648, entry 3374.
"Signé, Du Tillet"--Page 7.
"M" and "D" in date of publication are in apostrophic characters on title page.
Head-piece; initial.
Royal arms on title page.
Signatures: A⁴ (last page blank).
Keywords: Condé, Henri II de Bourbon, -- prince de, -- 1588-1646.; Condé, Henri II de Bourbon, -- prince de, -- 1588-1646.; 1610-1643; France; France -- Politics and government -- 1610-1643.; France -- History -- Louis XIII, 1610-1643 -- Pamphlets; History; Early works